New and Emerging Strategies in Platelet-Rich Plasma Application in Musculoskeletal Regenerative Procedures: General Overview on Still Open Questions and Outlook. (5th May 2015) - Salamanna, Francesca; Veronesi, Francesca; Maglio, Melania; Della Bella, Elena; Sartori, Maria; Fini, Milena
Abstract : Despite its pervasive use, the clinical efficacy of platelet-rich plasma (PRP) therapy and the different mechanisms of action have yet to be established. This overview of the literature is focused on the role of PRP in bone, tendon, cartilage, and ligament tissue regeneration considering basic science literature deriving from in vitro and in vivo studies. Although this work provides evidence that numerous preclinical studies published within the last 10 years showed promising results concerning the application of PRP, many key questions remain unanswered and controversial results have arisen. Additional preclinical studies are needed to define the dosing, timing, and frequency of PRP injections, different techniques for delivery and location of delivery, optimal physiologic conditions for injections, and the concomitant use of recombinant proteins, cytokines, additional growth factors, biological scaffolds, and stems cells to develop optimal treatment protocols that can effectively treat various musculoskeletal conditions.